Islam and Transgender (A Study of Hadith about Transgender) - Muh. Bahrul Afif (UIN Sunan Gunung Djati Bandung, 2019)
One of the issues that have been considered in the public sphere today is the issue of the transgender phenomenon. Transgender is related to the problem of gender identity. It refers to the condition in which the perpetrators identify their identity and gender differently from their sex biologically. It's caused by dissatisfaction and incompatibility between their body and soul. The term transgender might not be so familiar in Indonesia. However, to indicate that phenomenon, some of the people called them